Managing the spatial development of the Russian economy: Goals and tools - Evgeny M. Bukhvald (Ural State University of Economics, 2021)
The article substantiates the modern interpretation of spatial regulation of the economy. It determines the priorities and practical tools for managing spatial development, including the task of overcoming economic differentiation of Russian regions. The paper reveals the distinguishing features of spatial regulation policy in the context of the transition to the system of strategic planning. The theoretical and methodological basis of the study embraces the growth poles theory, the theory of new economic geography and the theoretical provisions of the Russian school of productive forces distribution, which made it possible to integrate the ideas of planned development of territories and market mechanisms of spatial self-regulation. Among the main research methods are economic-legal analysis and generalization. The system of regional development indicators constitutes the empirical basis of the study. The research results contain recommendations to clarify the provisions of the Spatial Development Strategy of the Russian Federation. In particular, the assessment of the economic differentiation of Russian regions, as well as its target values for the future should be added to the Strategy. We suggest classifying the types of federal constituent territories as objects of the state policy on regional development based on their economic characteristics. Moreover, it is expedient to overcome the current duality in the interpretation of the meso-level of strategic planning, and to design a state program for supporting towns through identification of specific needs of each type of settlement. The study also proposes to harmonize the legislation on strategic planning and on the fundamentals of the state policy on regional development with respect to priorities of economic equalization of regions, the emphasis on the federation subjects’ self-development, etc.